The Influence of Marketing Communication and Service Quality on Customer Decisions at BJB Syariah KCP Sumber Cirebon - Alvien Septian Haerisma; Abdul Ghoni; Dian Lestari (LPPM Universitas Terbuka, 2024)
Various studies have explored the impact of marketing communications and service quality on customer decisions. In carrying out its operational activities, Sharia banking has several factors that can influence the public to decide to use the products and services offered, these two factors include marketing communications and service quality. Therefore, this research aims to determine the influence of marketing communications and service quality on customers' decisions to use Wadiah IB Maslahah savings. The type of research used is survey research using a quantitative approach. The number of samples in this research was 70 samples. By using the Slovin formula, the standard error used is 0.1 or 10%. The data analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression tests, multiple coefficient tests, and hypothesis tests in the form of t-tests (partial) and F-tests (simultaneous), where all testing processes use IBM SPSS. The results of this research show that there is a partial positive and significant influence between marketing communication variables on customer decisions. Then there is a significant influence between service quality variables on customer decisions. And simultaneously marketing communication variables and service quality influence customer decision variables.